The paradox of thrombotic thrombocytopenic purpura and the TACO challenge! (Indian Journal of Case Reports, 2022)
Thrombotic thrombocytopenic purpura (TTP) is a rare medical emergency characterized by the pentad of microangiopathic hemolytic anemia, thrombocytopenia, fever, renal failure, and neurological dysfunction. TTP is an infrequent condition and is a thrombotic microangiopathy. TTP is essentially a clinical diagnosis. As untreated TTP has a high mortality, diagnosis is usually presumptive and prompt treatment with plasma exchange is highly beneficial and reduces mortality significantly. Therapeutic plasma exchange with fresh frozen plasma is the standard treatment of choice for TTP. Transfusion-associated reactions may occur in some patients further complicating the disease picture and prolonging hospital stay and recovery. Transfusion-associated circulatory overload and transfusion-associated acute lung injury are the leading cause of transfusion-related mortality. We present here the diagnostic and therapeutic challenges that we faced with a young male patient who presented with fever, jaundice, and seizures.